ANALISIS SIKAP DAN NORMA SUBYEKTIF TERHADAP PERILAKU KONSUMEN UNTUK MEMBELI SEPEDA MOTOR HONDA ABSOLUTE REVO (Studi Kasus: Masyarakat Kelurahan Bantan, Kecamatan Medan Tembung-Medan) Oleh: - Sinaga, Ria Veronica (Jurnal Manajemen dan Bisnis, 2018)
This study aims to determine and analyze the subjective attitudes and norms of consumer behavior to buy a Honda Absolute Revo motorcycle for the people of Bantan Village, Medan Tembung Sub-District. The benefits of research are to provide input for companies in order to formulate marketing strategies and contribute to researchers in the field of marketing science. Number of samples 96 respondents. Data collection techniques used were interviews, questionnaires and documentation. The data analysis method used is the Behavioral Intention (BI) Model. Based on the results of the study obtained the equation of interest in behavior (BI) as follows: BI = W1Ab + W2SN = 0.61Ab + 0.39SN. This means that greater behavioral interest is influenced by community attitudes of 0.61 (61%) from subjective norms of 0.39 (39%). Based on the description, it can be concluded that subjective attitudes and norms influence the behavior of the community in Bantan Village, Medan Tembung-Medan District in buying a Honda Absolute Revo motorcycle. We recommend that manufacturers of Honda Absolute Revo need to pay attention to the attitude of the people in buying motorbikes, especially affordable motorcycle prices, high resale prices, the excitement of fuel consumption, and ease of maintenance. Because these four attributes are the most dominant attributes affecting the attitude of the people to buy a Honda Absolute Revo motorcycle